Learning about Inclusive Practices in Higher Education – The Horizon of Asian Approaches - Horváth, Gergely (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Book: Sanger, C. S. & Gleason, N. W. (2020). Diversity and Inclusion in Global Higher Education – Lessons from Across Asia. Springer, Singapore.